Penerapan Prinsip Ekowisata Berkelanjutan dalam Pengembangan Ekowisata Berbasis Masyarakat di Desa Kunjir Kabupaten Lampung Selatan - Junaidi Junaidi; Anita Damayantie; Azis Amriwan; Handi Mulyaningsih; Muhammad Guntur Purboyo; Imam Mahmud (Nengah Nyappur, 2026)
Kunjir Village South Lampung Regency possesses considerable ecotourism potential through its coastal ecosystems, coral reefs, local culture, and community-based micro, small, and medium enterprises (MSMEs). However, the management of these resources has not been fully optimized due to limited public understanding of sustainable ecotourism principles, weak institutional capacity, and insufficient community participation in tourism management. This community service program aimed to strengthen community capacity in implementing sustainable ecotourism principles using a participatory approach. The activities consisted of field observation, Focus Group Discussions (FGD), brainstorming sessions, village potential mapping, training, and mentoring involving village officials, tourism managers, MSMEs, and local communities. Program evaluation was conducted through qualitative pre-test and post-test assessments to identify changes in participants' understanding. The results indicate significant improvement in community knowledge regarding environmental conservation, community empowerment, sustainable tourism management, and stakeholder collaboration. Furthermore, the program successfully identified the village's natural, cultural, historical, and creative economic assets that can be integrated into sustainable ecotourism packages. The program also generated strategic recommendations for strengthening local institutions, improving MSME competitiveness, and enhancing destination governance to support Kunjir Village as a sustainable and competitive ecotourism destination.